Analisis Rasio Prestasi Manajemen Irigasi pada Budidaya Tanaman Padi di Subak Kabupaten Tabanan - I Kadek Arya Santika; I Wayan Tika; I Putu Gede Budisanjaya (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2020)
Subak system is one form of irrigation system that is able to accommodate the dynamics of the sociotechnical system of the local community. Irrigation water is managed with the principles of justice, openness, harmony and togetherness, through a flexible organization that is in accordance with the interests of the community. Irrigation systems are closely related to the provision of irrigation water to rice cultivation plants. One aspect that will be assessed in an irrigation system is the Irrigation Management Performance Ratio (MPR). The purpose of this study is to determine the MPR classification in a subak by scoring in each MPR classification. The primary data was collected by interview, direct observation and measurement methods while secondary data was obtained from BMKG Region III Denpasar. The data that has been collected will then be rated and analyzed. Irrigation MPR for each subak is assessed using four ranges of values: Good if 0.75 <MPR<1.25, Sufficient if 0.60 1.60. The results of the analysis method of irrigation management achievement ratio in the cultivation of rice obtained by the upstream area MPR from periods I to VII irrigation management achievement ratio with an average value of 10.05 (Very Less) and for the middle area of irrigation MPR from period I to V the average value is 1.78 (Very Less), period VI with a value of 1.56 (Less), period VII with a value of 1.03 (Good) while for the downstream subak the MPR was obtained from the I to III periods with an average value of 2.25 (Very Less) and for periods IV to VII with an average value of 0.92 (Good).